Slow magic: agricultural R&D a century after Mendel - Pardey, Philip G.; Beintema, Nienke M. (International Food Policy Research Institute, 2001)
This report assembles and assesses new evidence regarding investments in agricultural R&D, tracking global trends over the past several decades, and highlighting the critical importance that the accumulated stock of scientific knowledge has for today’s productivity and for future innovations and economic growth.